2019
DOI: 10.1055/s-0039-1698805
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Expectations of Patients Undergoing Knee Surgery

Abstract: There is limited validated data regarding the relationship between preoperative expectations and patient-reported outcomes (PROs) in patients undergoing knee surgery. The purpose of this study was to (1) assess the preoperative expectations of patients undergoing knee surgery and (2) determine the relationship between preoperative patient demographics, PROs, and preoperative patient expectations. We hypothesized that younger patients with worse function and worse general health status would have greater expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 38 publications
(65 reference statements)
0
14
0
Order By: Relevance
“…To this end, in a recent series of nearly 400 patients who underwent elective knee surgeries, the authors reported that lower patient-reported preoperative pain and disability correlated with increased preoperative expectations, suggesting that patients with more preoperative pain may have a lower threshold for perceived improvement than those with higher expectations. 40 We also determined that presence of at least 1 DSM-5 behavioral health diagnosis—the most common being anxiety and/or depression—resulted in less ankle pain relief and higher incidence of clinical failure following PJCAT. While this finding may be controversial and novel as it relates to PJCAT outcomes, it is by no means unique.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, in a recent series of nearly 400 patients who underwent elective knee surgeries, the authors reported that lower patient-reported preoperative pain and disability correlated with increased preoperative expectations, suggesting that patients with more preoperative pain may have a lower threshold for perceived improvement than those with higher expectations. 40 We also determined that presence of at least 1 DSM-5 behavioral health diagnosis—the most common being anxiety and/or depression—resulted in less ankle pain relief and higher incidence of clinical failure following PJCAT. While this finding may be controversial and novel as it relates to PJCAT outcomes, it is by no means unique.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, confounding variables such as age, comorbidities, and patient expectations may have influenced preoperative clinical outcome scores for inpatient TAR. 11,46…”
Section: Discussionmentioning
confidence: 99%
“…We chose to include adolescents to better elucidate any possible relationships between age and expectations and the youngest patient in the cohort was 15 years old. 35,36 All enrolled patients were given the following questionnaires preoperatively: Patient-Reported Outcome Measurement Information System (PROMIS) PF, PROMIS pain interference, PROMIS fatigue, PROMIS social satisfaction, PROMIS anxiety, PROMIS depression, Brief Michigan Hand Questionnaire, MODEMS expectations questionnaire, Tegner activity scale (Tegner), Marx activity rating scale, and numeric pain scale (NPS) for both the operative hand and the rest of the body. MODEMS asks patients what results they expect from their treatment on a five-point Likert scale ranging from "not at all likely" (1) to "extremely likely" (5).…”
Section: Methodsmentioning
confidence: 99%